Effect of Rowatinex on Calculus Clearance After Extracorporeal Shock Wave Lithotripsy - Djaladat, Hooman; Mahouri, Khatereh; Khalifeh Shooshtary, Fatemeh; Ahmadieh, Azadeh (Urology Journal, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Introduction: our aim was to evaluate the effect of Rowatinex, an essential oil preparation of terpenic type, on kidney calculi clearance after extracorporeal shock wave lithotripsy (SWL). Materials and Methods: A randomized controlled trial was performed at Hormozgan Hospital in Bandar Abbas, Iran, on 100 patients with 10-mm to 20-mm kidney calculi. They underwent SWL, and then, they were randomly assigned into 2 groups to receive either Rowatinex, 100 mg, 3 times per day, or placebo after SWL. Patients were followed up with plain abdominal radiography, ultrasonography, and excretory urography (if required), 2 and 4 weeks postoperatively. Results: Two weeks following SWL, 6 (12%) and 9 (18%) patients in the Rowatinex and control groups had fragmented calculi without clearance, 26 (52%) and 24 (48%) had less than 50% clearance, 9 (18%) and 15 (30%) had more than 50% but not total clearance, and 9 (18%) and 2 (4%) patients were stone free, respectively. Rowatinex had a significant effect on the stone-free rate (P = .02). Four weeks post-SWL, 3 (7.3%) and 7 (14.6%) other patients in the Rowatinex and control groups became stone free, respectively. Overall, Rowatinex had no significant effect on the stone-free rate (P = .46). No complications or differences between the two groups in symptoms and signs were reported. Conclusion: Rowatinex does not have a significant effect on clearance rate of kidney calculi after SWL. However, it can accelerate calculus passage after 2 weeks, and it does not have any significant adverse effects.